دور تبعية المدقّق الداخلي التنظيميّة في تحقيق استقلاليّته المهنية _ دراسة مسحية في القطاع العامّ_ (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يهدف هذا البحث إلى التحقّق من دور تبعيّة المدقّق الداخليّ التنظيميّة في تحقيق استقلاليّته المهنية في جهات القطاع العامّ الإدارية والاقتصادية في سورية باعتماد استبيان وُزّع على عينة عشوائية من العاملين فيها ضمن مواقع ومراكز متنوعة. وقد أكّدت نتائج الدراسة المسحية صحّة جميع فرضيات الدراسة في أن يتبع المدقق الداخلي إلى إحدى الجهات المقترحة من قبل الدراسة، وهي: مجلس الإدارة، والهيئة المركزيّة للرقابة والتفتيش، والجهاز المركزيّ للرقابة المالية. بيد أنّ تبعية المدقّق الداخليّ التنظيمية إلى الهيئة المركزية للرقابة والتفتيش حظيت باهتمامٍ أكبر من نظيراتها، ومن ثمّ تعدّ أفضل الحلول المقترحة لتعزيز استقلاليته المهنية، مع التركيز على عملية تعيين المدقّق الداخليّ التي تمثّل التهديد الأكبر لاستقلاليته من وجهة نظر عينة الدراسة. This research aims to verify the role of the organizational dependence of the internal auditor in achieving his professional independence on the administrative and economic public sector in Syria by filling in a questionnaire distributed to a random sample of employees in different sites and centers. The results of the field study confirm the validity of all study hypotheses which say that the internal auditor must be related to one of the parties proposed by the study which are: the Board of Directors, the central body of supervision and inspection, the Central Agency for Financial Control. However The internal auditor dependence to the central body of supervision and inspection had greater attention by the study sample, with a focus on the appointment process, which represents the biggest threat to the professional independence of the internal auditor from the viewpoint of the study samples